Dos Cursos complementares aos cursos clássico e científico: A mudança na Organização dos ensinos de matemática - Ribeiro, Denise Franco Capello (2006)
The aim of this search is to add to the investigations about the mathematic education history in Brazil, especially in the age from 1930 to 1940. The purpose is the happened transformations of the Mathematic teaching organization from the Complementary Grades, established in the Francisco Campos reform to the Classic and the Scientific Grades, established in the Gustavo Capanema s reform. Well-founded in the theoretical lessons of André Chervel, Alain Choppin and Roger Chartier, the study asks the question: What happened transformations in the mathematic teaching organization, from the Francisco Campos reform to the Capanema s? To answer this question, we use the legislation of the educational reforms and the Mathematic s books of the studied age as principal search authority